2019
DOI: 10.1186/s12998-019-0284-5
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge of psychosocial factors associated with low back pain amongst health science students: a scoping review

Abstract: BackgroundLow back pain is a burden worldwide and biological, psychological, and social mechanisms play a role in its development and persistence. Current guidelines support care using the biopsychosocial model. However, biomedical constructs dominate clinician training, and it is unknown the extent to which health science students understand the psychosocial determinates of a patient’s low back pain. Therefore, the aim of this scoping review is to report health science students’ current knowledge of psychosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The authors concluded that physicians and nurses had a stronger belief that low back pain causes disability and activity limitation than physiotherapists and occupational therapists. In another study (27) evaluating the attitudes and beliefs of senior students in physiotherapy and rehabilitation, medicine, and nursing using BBQ, physiotherapy (28) reported that physiotherapy and rehabilitation students had more positive beliefs than those studying in the remaining disciplines. In the current study, we observed more pessimistic beliefs concerning CLBP among the family physicians compared to the physiotherapists, and among the physiotherapists compared to the physiatrists based on the BBQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that physicians and nurses had a stronger belief that low back pain causes disability and activity limitation than physiotherapists and occupational therapists. In another study (27) evaluating the attitudes and beliefs of senior students in physiotherapy and rehabilitation, medicine, and nursing using BBQ, physiotherapy (28) reported that physiotherapy and rehabilitation students had more positive beliefs than those studying in the remaining disciplines. In the current study, we observed more pessimistic beliefs concerning CLBP among the family physicians compared to the physiotherapists, and among the physiotherapists compared to the physiatrists based on the BBQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant translational gap between knowledge of the contribution of psychosocial factors to SRDs and implementation in the training of all healthcare disciplines, including chiropractic. To point, a recent scoping review found substandard awareness amongst all health science students (e.g., chiropractic, physical therapy, medical) with respect to psychosocial factors and low back pain [ 8 ]. Without tangible changes at the educational level, this gap is unlikely to narrow.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these guidelines, adoption of the BPS model in chiropractic care settings is arguably incomplete [ 6 , 7 ]. Furthermore, students across various healthcare disciplines, including chiropractic, have a poor awareness of these psychosocial factors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An electronic database search strategy was developed with a health sciences librarian and searches were conducted in MEDLINE, EMBASE, CINAHL from inception until March 1, 2021, with no language restriction. The search strategy and search terms were informed by previous reviews on patient centred care [ 12 ] and healthcare students [ 13 ]. Our search strategy combined terms relating to ‘patient centred care’, ‘attitudes’, and ‘healthcare students’ and was designed to capture studies investigating healthcare students attitudes towards patient centred care as per our preregistered protocol.…”
Section: Methodsmentioning
confidence: 99%